THE ABSENCE OF A HASH SUM AS A PROCEDURAL ERROR ARISING IN A FORENSIC EXAMINATION WHEN ANALYSING OBJECTS IN A DIGITAL FORM - SHIKHALIYEVA Seldjan Zaur qizi (Правовое государство: теория и практика)
An urgent task when working with digital objects is to comply with procedural rules and regulations in appointing a forensic examination and conducting research. Failure to comply with them leads to procedural errors, one of which is the failure to specify the hash sum of a digital file in the ruling on the appointment of the expert examination and in the expert report itself. Purpose: to analyse a procedural error committed by investigators and experts when describing a digital footprint; to identify the importance of specifying the hash sum as an identifying characteristic; to suggest ways of preventing this error. Methods: empirical methods of comparison, description, interpretation; theoretical methods of formal and dialectical logic. Results: the article reveals a procedural error associated with the illiterate description of a digital object sent for expert examination, and based on the analysis of judicial and expert practice the preconditions leading to its occurrence are identified; measures to prevent such errors are proposed.